Novel TBC1D24 Mutations in a Case of Nonconvulsive Status Epilepticus - Li, Jingjing; Liu, Ruihong; Feng, Huiyu; Zhang, Jian; Wang, Dilong; Wang, Yiming; Zeng, Jinsheng; Fan, Yuhua (Frontiers in Neurology, 2018)
Objective Nonconvulsive status epilepticus (NCSE) is an uncommon clinical manifestation in patients with TBC1D24 mutations. In addition, NCSE has not been reported as a syndrome together with cerebellar ataxia and ophthalmoplegia. Methods Here, we report the clinical and genetical features of a 4-year-old patient with NCSE, cerebellar ataxia and ophthalmoplegia caused by novel TBC1D24 mutations. We performed 24hour-video electroencephalogram (EEG) result, MR imaging and gene sequencing for the patient and her parents to diagnosis. Results In this patient, We identified the novel c.1416_1437del (p.Ser473Argfs*43) mutation and known c.1499C>T (p.Ala500Val) mutation in TBC1D24 by using targeted Next-Generation Sequencing. The novel mutation (inherited from mother) is also the first reported deletion mutation longer than 20 bp in TBC1D24. The p.Ala500Val mutation inherited from father have been reported in a German patient with infantile myoclonic, normal EEG and normal neuroimaging. This mutation plus the novel maternal truncated mutation, p.Ser473Argfs*43, resulted in the severe phenotypes in our patient. Conclusions We proved the novel TBC1D24 mutation which is also the first reported deletion mutation longer than 20 bp in TBC1D24.In addition, the patient is characteristic of the complicated clinical manifestation. It suggest that we should pay more attention to the patient with NCSE and ataxia and genetic test should be performed in these patients to avoid the genetic inheritance.